Disaster management Antique's experience - Pancubila, Ricardo S.
Executive summary-This research entitled "Disaster Management : Antique's Experience" had the following objectives : determine the organizational structure adopted by the LDCCs in the province of Antique, identify the disaster management policies promulgated by the LDCCs that could enhance the smooth operationalization of its functions before, during and after the occurrence of disasters, identify the plans and programs developed and undertaken by the LDCCs to strengthen their disaster prevention, mitigation and rehabilitation efforts, determine the availability of logistics and resources for immediate deployment during emergency cases, and assess the adequacy of the LDCCs mechanism applied during the different disaster phases. To attain these, a survey was conducted among the members of the LDCCs in the Province of Antique. Used as a source of data was a questionnaire which had undergone validation and the revision were made based on the suggestions given by the professor. Upon retrieval of the accomplished questionnaires, the data were tallied, computed and analyzed. Analyses of the data revealed that all the five issues discussed have great impact on the preparedness of the LDCCs in the province.